Establishing absorbed energy spectra-an attenuation approach. - Chou, Chung-Che (Earthquake engineering & structural dynamics.)
For energy based seismic design, energy demand in the form of absorbed energy spectra was established by an attenuation relationship. The absorbed energy is proposed for evaluating the energy demand in an inelastic system because the absorbed energy is directly related to the pseudo-velocity in the elastic case. Based on a total of 273 ground motion records from 15 significant earthquakes in California, an attenuation relationship of the absorbed energy was established from a two stage non linear regression analysis. This relationship was established for a given earthquake magnitude, source to site distance, site class and ductility factor. A similar expression for the normalized absorbed energy was also developed. This study showed that the absorbed energy for near field ground motions can be significantly larger than that predicted by the attenuation relationship for normal ground motions.